An Architecture of Calcium Signaling for Molecular Communication Based Nano Network - Mukherjee, Amitava; Das, Sushovan; Chatterjee, Soumallya (Modeling, Methodologies and Tools for Molecular and Nano-scale Communications, 2017)
The Nobel laureate physicist Richard Feynman, in his famous speech in 1959 entitled “There’s Plenty of Room at the Bottom”, has pointed out the concepts in nanotechnology and described how the manipulation of individual atoms and molecules would give rise to more functional and powerful man-made devices.